Enhancement of stability margin based on dynamic brake strategy - Majli Nema Hawas (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The Rate of Change Kinetic Energy (RACKE) method achieves considerable reduction in computing time by virtue of the way that it does not need the solution of system equation beyond fault clearing time. In RACKE method the machine which tends to lose synchronism can be defined as that which has the largest negation RACKE value. The injection of the brake ought to be achieved when RACKE of the machine liable to be unstable reaches its maximum negative value. Elimination happens when RACKE of the machine is zero and disturbance angular velocity passes through zero changing sign from positive to negative. To defining the instant of injection and elimination of brake, RACKE method can be used to investigate the transient stability margin of a power system through evaluation of RACKE value at the instant of fault clearance. The simulation demonstrates that the applying of a braking resistor at the terminal of each of the machines, pulling of synchronism, simultaneously brings the system into stable trajectory. It is clear from the results obtained that dynamic braking depending on the RACKE criterion for insertion and removal of the brake gives excellent results in an enhancement of transient stability margin.